Unlocking the market [with mobile apps] - Odhiambo, Fredrick (Technical Centre for Agricultural and Rural Cooperation, 2014)
A 2013 study entitled Market in their Palms conclusively shows that the use of mobile apps by smallholder farmers in Kenya has helped them to gain access to markets and market information and improved their businesses